Making Sense of Quantum Mechanics by Jean Bricmont - Williams III, George Robert (Journal of Scientific Exploration, 2017)
Quantum mechanics is both perhaps our most successful scientific theory and the least understood. The standard or Schrödinger equation of quantum mechanics fits the experimental data remarkably well. Within the traditional (Copenhagen) framework, this equation describes the evolution of a wave function (a grouping of potential states) until a measurement discontinuously triggers the wave function to “collapse” into the observation of an experiment. As is well known, this interpretation provides no mechanism or ontology to account for this instantaneous collapse. Currently, there is no consensus that favors an interpretation for this measurement problem. Jean Bricmont’s Making Sense of Quantum Mechanics is a welcome contribution toward helping us navigate through the complex and paradoxical nature of quantum mechanics, as well as the various attempts to explanation it. While Bricmont offers a great deal of technical rigor, he focuses on the conceptual problems in a relatively straightforward and accessible way. To be clear, Bricmont does not eschew mathematics. However, the level of mathematics involved here is what would typically be required in a first or second year course for scientists and engineers: linear algebra, complex numbers, Fourier transforms, basic differential equations, and classical mechanics. And most of the formal proofs and analyses are relegated to the appendices. In addition, many technical aspects and references to more advanced literature are placed in the footnotes. This book is therefore organized in a way to serve a wide range of interested readers.